A method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core
By using modified salt powder and nano-ceramic particles for impregnation in the droplet injection molding process, the problems of high temperature decomposition and salt moisture absorption in traditional core preparation are solved, and the high strength, low porosity and high precision of the core are achieved.
Patent Information
- Application Number
- CN202410586297.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-13
AI Technical Summary
In the prior art, traditional impregnation liquid will decompose at high temperatures to affect the core performance and accuracy, and the salt in the core raw material will absorb moisture during printing and storage, affecting the quality of the core.
The micro-droplet injection molding process is used to mix ceramic powder and modified salt powder to prepare the core. Nano-ceramic particles and salt solution are used to fill the core pores through the impregnation process, and the molten salt flows to fill the pores during high-temperature sintering to increase the density of the core. and intensity.
It significantly improves the strength and thermal stability of the core, reduces porosity and sintering shrinkage, and ensures the dimensional accuracy and solubility of the core.
Smart Images

Figure CN118492277B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rapid casting, and in particular to a method for improving the performance and precision of a soluble core formed by micro-droplet injection molding, and the soluble core. Background Art
[0002] Engine casings and turbine blades are indispensable parts in the fields of aerospace and aviation. These parts have complex cavity structures. In order to form the cavity structure, cores are required in the casting process of the parts. The performance and precision of the cores also affect whether these parts can be used. The traditional core preparation methods such as injection molding, isostatic pressing and gel injection molding mentioned in patents CN202211249829.6 and CN202310932619.5 require the preparation of molds during preparation, with a long preparation cycle and low production efficiency. There are certain difficulties in molding complex cores. Traditional alumina and silicon oxide-based ceramic cores need to be de-cored by mechanical vibration, alkali corrosion and other methods after pouring, but these methods will have an adverse effect on the quality of the castings, and the effect is not ideal when removing complex curved cores. The de-coring liquids mentioned in patents CN202310986691.6 and CN201810606149.2 are all strong alkalis, and the de-coring process needs to be carried out under high temperature and high pressure, which is a complicated process. Therefore, it is necessary to develop an efficient core preparation method and an easily removable core material.
[0003] Droplet jet bonding molding technology is an advanced 3D printing technology and a type of powder bed fusion technology. This technology uses a nozzle to precisely control the spraying of a binder onto a powder bed to build a three-dimensional object layer by layer. The existing patent CN117383916A discloses a soluble ceramic core, a preparation method and an application. By combining ceramic powder and a soluble salt, a ceramic core blank is printed using droplet jet bonding molding technology, and a soluble ceramic core is obtained by high-temperature sintering. Although the ceramic core prepared by the above scheme has good solubility, it can improve production efficiency and reduce costs.
[0004] However, the above scheme still has the following shortcomings: (1) Since the packing density of powder with a single particle size is relatively low, the porosity of the printed body is relatively high. In order to ensure that the core has a certain strength, an infiltration treatment is required. The traditional infiltration liquid is generally a dispersion or sol of nano-ceramic particles. These nano-ceramic particles are different from the ceramic particles in the printing raw materials. The strengthening mechanism is mainly that the ceramic particles in the infiltration liquid react with the ceramic particles in the core at high temperature to generate new substances. These newly generated substances will improve the performance of the core. However, this reaction temperature is often much higher than the melting point of the salt, which will cause a large amount of salt in the core to decompose and volatilize, affecting the strength and solubility of the core after sintering. In addition, the large amount of salt decomposition will also cause the core to shrink too much after sintering, affecting the dimensional accuracy of the core after sintering. (2) The powder with a single particle size makes the packing density of the powder bed low during the printing process, resulting in a large porosity of the printed body. At the same time, the salt in the printing raw materials is very easy to absorb moisture, which will affect the printing process and core storage. Summary of the invention
[0005] In view of this, the present invention proposes a method for improving the performance and precision of a soluble core formed by droplet injection molding and a soluble core, so as to solve the technical problems in the prior art that the traditional impregnation liquid will decompose at high temperature and affect the performance and precision of the core, and the salt in the core raw material will absorb moisture during printing and storage.
[0006] The technical solution of the present invention is implemented as follows: The present invention provides a method for improving the performance and precision of a soluble core formed by droplet injection, comprising the following steps:
[0007] S1, mixing ceramic powder and modified salt powder to form a mixed powder, using a droplet injection molding process to prepare a core blank from the mixed powder, and heating and curing to obtain a core blank;
[0008] S2, preparing a soluble salt solution, and adding nano-ceramic particles to the soluble salt solution, and mixing to obtain an impregnation solution;
[0009] S3, placing the core blank into an impregnation liquid for impregnation treatment, drying and then sintering at high temperature, and cooling in the furnace to obtain a soluble core.
[0010] In the present invention, in step S1, a droplet jet forming process is adopted to prepare a soluble core with ceramic powder and salt as raw materials, wherein the salt provides the solubility characteristics of the core, and the ceramic powder enhances the mechanical strength and thermal stability of the core. The above scheme has the advantages of high efficiency, no need for supporting materials in the forming process, and the ability to quickly form a complex structure core. At the same time, after pouring, the salt in the core will dissolve in water and the core will collapse, thereby realizing the efficient removal of the core. This can solve the problems of long production cycle and difficulty in forming complex shapes in traditional preparation methods, and can solve the problems of complex core removal process, unsatisfactory core removal effect, and easy damage to castings. In steps S2 and S3, salt and nano ceramic particles are mixed in a certain proportion to form an impregnation solution. After the core blank is infiltrated, the salt and nano ceramic particles in the solution will fill the pores of the blank, reduce the porosity of the core, and increase the relative density. During high-temperature sintering, the molten salt flows inside the core and fills the pores, making the internal structure of the core denser. At the same time, the ceramic particles in the core are surrounded by molten salt, which also plays a role in particle strengthening. These greatly improve the strength of the core, which is 5 times higher than that of the untreated core. The addition of nano-ceramic particles can also improve the thermal stability of the core and reduce thermal stress problems during the casting process.
[0011] On the basis of the above technical solution, preferably, the preparation process of the modified salt powder is as follows:
[0012] The modifier and the organic solvent are mixed to obtain a modified solution, and then the soluble salt is added to the modified solution, stirred at 25-50° C., and the modified salt powder is obtained by drying and crushing. The particle size of the modified salt powder is 200 mesh-2000 mesh, wherein the mass volume ratio of the soluble salt to the organic solvent is 1:3-6, and the organic solvent is an alcohol solvent, including but not limited to anhydrous ethanol, anhydrous methanol, etc.; the amount of the modifier added is 5%-15% of the mass of the soluble salt.
[0013] The modified solution is a solution formed by dissolving oleic acid and / or stearic acid accounting for 5%-15% of the mass of the soluble salt in anhydrous ethanol; the mass volume ratio of the soluble salt to the modified solution is 1:3-6.
[0014] On the basis of the above technical scheme, preferably, the composition of the soluble salt includes, by mass percentage, 10%-20% of calcium salt and 80%-90% of other salts, the other salts include one or a mixture of several of chlorides, sulfates, silicates, phosphates and metaphosphates, and the calcium salt is calcium chloride and / or calcium nitrate.
[0015] During the modification process, oleic acid and stearic acid react with calcium ions in soluble salts to form calcium oleate and calcium stearate. These reactions mainly occur on the surface of the salt, and the generated calcium oleate and calcium stearate form a stable coating on the surface of the salt. This coating not only physically isolates the direct contact between the salt and the external environment (especially moisture), but also reduces the adsorption of moisture through its hydrophobic properties. The coating on the surface of the modified salt powder effectively prevents the salt from contacting with moisture in the air, significantly improving the salt's resistance to hydration. This feature can maintain the fluidity and processability of the powder and prevent the formation of lumps caused by salt moisture absorption during printing. At the same time, this treatment is particularly important for storage and handling in a humid environment, which can effectively prevent the core blank from cracking due to moisture absorption during storage. During high-temperature sintering, calcium oleate and calcium stearate will decompose. The decomposition products of these substances are mainly calcium salts, CO2 and other harmless gases, which will escape during the sintering process and will not leave residues that are harmful to the core structure. The presence of calcium salts will not have an adverse effect on the performance and solubility of the core.
[0016] On the basis of the above technical solution, preferably, the particle size of the ceramic powder is 200 mesh-2000 mesh, and the mass percentage of the ceramic powder in the mixed powder is 10%-90%.
[0017] On the basis of the above technical solution, preferably, the ceramic powder includes a mixture of two or more particle sizes, and each particle size accounts for more than 15%. The ceramic powder can be a mixture of any multiple particle sizes within the range of 200 mesh-2000 mesh, such as 200 mesh, 500 mesh and 1000 mesh ceramic powder powders are mixed in a ratio of 25%, 30% and 45% respectively; or 200 mesh, 500 mesh, 1000 mesh, 1500 mesh, 1200 mesh are mixed in a ratio of 20%, respectively, and the present invention is not specifically limited here.
[0018] More preferably, the ceramic powder is one or a mixture of powders such as silicon dioxide, aluminum oxide, zirconium oxide, and yttrium oxide.
[0019] Specifically, using two or more particle sizes in ceramic powder and ensuring that each particle size accounts for at least 15% can achieve more uniform and dense powder stacking. When powder particles of different particle sizes are stacked, larger particles form a framework structure, while smaller particles fill the gaps between larger particles. This distribution helps to reduce porosity. Powders of different particle sizes can fuse better during the sintering process to form a tighter connection between particles. This close connection helps to improve the overall structural strength of the core, while reducing sintering shrinkage to a certain extent, because fewer gaps between materials can reduce the movement and reorganization of materials during sintering.
[0020] On the basis of the above technical scheme, preferably, in step S3, the impregnation treatment time is 40s to 4min, the impregnation method is normal pressure impregnation or vacuum impregnation, and the vacuum degree during vacuum impregnation is 0 to 40KPa; in step S2, the soluble salt solution is a saturated or supersaturated solution of soluble salt powder, and the soluble salt powder has the same composition as the modified salt powder in step S1.
[0021] Specifically, the impregnation time is adjusted according to the size and pore structure of the core blank. A shorter time is sufficient for the impregnation liquid to penetrate into the surface and shallow structure of the core, while a longer time allows the liquid to penetrate deeper into the internal structure. The above control of the impregnation time helps to ensure the uniform distribution of the liquid and avoid structural problems caused by excessive impregnation. Normal pressure impregnation is suitable for penetration without extreme conditions, while vacuum impregnation (vacuum degree 0-40KPa) is used for more difficult penetration situations, such as cores with high porosity or complex internal structures. Vacuum can help remove air and other gases in the core, thereby promoting deeper penetration of the liquid. Saturated solutions ensure that there are enough modified salts in the solution so that they can fully enter the core blank during the impregnation process. Supersaturated solutions contain more solutes than saturated solutions, which can form a thicker salt layer on the surface of the core, which helps to form a more solid structure in subsequent processing. At the same time, the use of saturated or supersaturated solutions of salt can prevent collapse and disintegration due to the dissolution of salt inside the core blank in water during the infiltration process, thereby ensuring the integrity of the core.
[0022] On the basis of the above technical scheme, preferably, the particle size of the nano-ceramic particles in step S2 is 15-100nm, the amount of the nano-ceramic particles added is 5%-20% of the mass of the soluble salt solution, and the nano-ceramic particles are one or a mixture of nano-silicon dioxide, nano-alumina, nano-zirconium oxide, and nano-yttrium oxide.
[0023] Nano-ceramic particles can penetrate into the tiny pores of the core material due to their tiny size, which helps to form a denser structure in the pores, reduce porosity, and improve the overall mechanical strength and thermal stability of the core; nano-ceramic particles can promote more uniform heat distribution during sintering, reduce thermal stress, improve the heat resistance of the core, and reduce the possibility of thermal deformation and thermal cracking of the core material during high-temperature casting. Nano-ceramic particles will play a pinning role inside the core, inhibit the abnormal growth of internal grains, refine the grains, and thus play a role in fine grain strengthening in the core. Adding too few nano-ceramic particles may not be able to fully provide sufficient strength and thermal stability, and adding too many may cause the impregnation solution to be too thick, affecting its fluidity and ability to evenly infiltrate the core.
[0024] On the basis of the above technical scheme, preferably, in step S1, in the droplet injection molding process, the binder is phenolic resin, the binder saturation is 90%-150%, the printing layer height is 0.07mm-0.25mm; the heating curing temperature is 190℃-220℃, and the heating curing time is 2h-5h.
[0025] Phenolic resin is used as a binder. When heated and cured, the phenolic resin will undergo a curing reaction, which gives the core blank a certain initial strength, prevents the core blank from breaking or deforming, and ensures the subsequent infiltration and sintering process. Selecting a layer height between 0.07mm-0.25mm can achieve a good balance, ensuring the surface quality and detail accuracy of the core while completing the printing within a reasonable time. Curing at 190℃-220℃ can ensure that the resin is fully cured and improve the mechanical strength and thermal stability of the core. The choice of curing time (2h-5h) ensures that the resin can be evenly cured throughout the core, avoiding structural weaknesses that may be caused by uncured areas.
[0026] On the basis of the above technical solution, preferably, in step S3, the sintering is divided into two stages, namely, sintering at 550°C-700°C for 2h-3h, and then sintering within ±50°C of the melting point of the salt for 2h-3h, and the heating rate during the sintering process is 2-6°C / min.
[0027] In the first stage, within this temperature range, the organic components in the phenolic resin begin to decompose and pyrolyze, releasing small molecule volatiles. Preliminary sintering at a lower temperature can control the decomposition rate of organic matter, avoid internal stress and defects (such as cracks) caused by rapid decomposition, and help maintain the structural integrity and shape stability of the core. In the second stage, sintering at a temperature close to the melting point of the salt, the highest temperature of the infiltrated blank only needs to be near the melting point of the salt during high-temperature sintering. At this temperature, the salt will not decompose and volatilize basically, and the molten salt will fill the internal pores of the core, reducing the shrinkage caused by particle migration during sintering. Therefore, the core after sintering will not produce a large shrinkage, and the shrinkage rate can be controlled below 2%, and the dimensional accuracy is guaranteed. At the same time, the salt inside the core is basically not decomposed, which also ensures that the core has good solubility.
[0028] In a second aspect, the present invention provides a soluble core, which is prepared by a method for improving the performance and precision of a soluble core in droplet injection molding as described in any of the above items.
[0029] The method for improving the performance and precision of a soluble core for droplet injection molding and the soluble core of the present invention have the following beneficial effects compared with the prior art:
[0030] (1) Using droplet jet bonding forming technology, the preparation of soluble cores with ceramic powder + salt as raw materials has the advantages of high efficiency, no need for supporting materials during the forming process, and the ability to quickly form complex structure cores. At the same time, after pouring, the salt in the core will dissolve in water and cause the core to collapse, thereby achieving efficient removal of the core. This can not only solve the problems of long production cycle and difficulty in forming complex shapes in traditional preparation methods, but also solve the problems of complex core removal process, unsatisfactory core removal effect, and easy damage to castings;
[0031] (2) After the core blank is infiltrated, the salt and nano-ceramic particles in the solution will fill the pores of the blank, reduce the porosity of the core, and increase the relative density. During high-temperature sintering, the molten salt flows inside the core and fills the pores, making the internal structure of the core denser. At the same time, the nano-ceramic particles in the core will inhibit the abnormal growth of grains and play a role in fine grain strengthening. These greatly improve the strength of the core, which is 5 times higher than that of the untreated one;
[0032] (3) The highest temperature of the infiltrated green body during high-temperature sintering only needs to be near the melting point of the salt. At this temperature, the salt will basically not decompose and volatilize. At the same time, the molten salt will fill the pores inside the core, reducing the shrinkage caused by particle migration during sintering. Therefore, the core will not shrink significantly after sintering, and the shrinkage rate can be controlled below 2%, and the dimensional accuracy is guaranteed. At the same time, the salt inside the core has basically not decomposed, which also ensures that the core has good solubility;
[0033] (4) The printing raw material obtained by mixing ceramic powders of various particle sizes uniformly after grading has a greatly improved packing density of the powder bed during the printing process, which not only reduces the porosity of the printed core blank, but also makes the particles inside the core tightly connected, thus reducing the sintering shrinkage of the core to a certain extent;
[0034] (5) After the soluble salt is modified, oleic acid, stearic acid, etc. will react with the Ca in the salt. 2+ The reaction generates substances such as calcium oleate and calcium stearate, which will form a coating on the surface of the salt to prevent the salt from contacting with moisture in the air, thereby improving the hydration resistance of the raw material. At the same time, during the sintering process, calcium oleate, calcium stearate and excess stearic acid will decompose at high temperatures and will not have an adverse effect on the core. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 The present invention is a flow chart of a method for improving the performance and precision of a soluble core formed by micro-droplet injection molding. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core, which specifically includes the following steps:
[0040] S1, 80g sodium chloride and 20g calcium chloride were mixed evenly, and then the salt was put into 500ml stearic acid ethanol solution, the mass of stearic acid in the solution was 10g, stirred evenly and dried to obtain modified salt particles, and then the modified salt particles were crushed into 1000 mesh to obtain modified salt powder;
[0041] S2. Evenly mix 1000-mesh silica and modified salt powder as printing materials, wherein the modified salt powder is added in an amount of 40%. Spread the mixed powder over the powder supply cylinder, import the three-dimensional structure model of the ceramic core into the computer, and adjust the various printing parameters of the 3D printer. Then start printing, and the nozzle, powder supply cylinder, and working cylinder run according to the set program until the printing process is completed. Among them, the printing parameters of the 3D printing equipment are: printing layer height 0.07mm, binder is phenolic resin, and binder saturation 90%;
[0042] S3. After printing, place the printed core body together with the powder bed in a drying oven and heat and cure at 190°C for 3 hours. After cooling, remove the core body from the powder bed and clean up the excess powder around it. Use a saturated solution of sodium chloride and calcium chloride as the infiltration liquid, with a mass ratio of sodium chloride to calcium chloride of 4:1. Then place the core body in the infiltration liquid, take it out after infiltration for 3 minutes at normal pressure, and then place it in a drying oven to dry;
[0043] S4, the infiltrated ceramic body is placed in a crucible, and is completely filled with spherical alumina particles, and then placed in a muffle furnace for high-temperature sintering. The sintering curve is sintered at 550°C for 2h, sintered at 20°C above the melting point of sodium chloride for 2h, and the heating rate is 2°C / min. Finally, the soluble core is obtained by cooling with the furnace.
[0044] Example 2
[0045] The present embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core. The specific preparation method is the same as that of Example 1, except that: in step S3, the immersion liquid is a saturated solution of sodium chloride and calcium chloride, to which 50 nm silicon dioxide particles are added and evenly dispersed, wherein the amount of silicon dioxide particles added is 15% of the total mass of the saturated solution of sodium chloride and calcium chloride.
[0046] Example 3
[0047] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core, such as Figure 1 As shown, the specific preparation method is the same as Example 2, except that: in step S1, the modified salt particles are crushed into 200 mesh, 500 mesh and 1000 mesh, and in step S2, the 200 mesh, 500 mesh, 1000 mesh silica and modified salt powders are evenly mixed as printing raw materials, wherein the proportions of 200 mesh, 500 mesh, and 1000 mesh powders are 25%, 30%, and 45%, respectively.
[0048] Example 4
[0049] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core, which specifically includes the following steps:
[0050] S1, mix 90g sodium sulfate and 10g calcium chloride evenly, then put the salt into 300ml stearic acid ethanol solution, the mass of stearic acid in the solution is 12g, stir evenly and dry to obtain modified salt particles, then crush the modified salt particles into 200 mesh, 500 mesh, 1000 mesh, and 1500 mesh to obtain modified salt powder.
[0051] S2, mix 200 mesh, 500 mesh, 1000 mesh, 1500 mesh silica and modified salt powder evenly as printing raw materials, wherein the modified salt powder is added in an amount of 10%, and the proportions of 200 mesh, 500 mesh, 1000 mesh, and 1500 mesh powders are 15%, 25%, 25%, and 35%, respectively. Spread the mixed powder over the powder supply cylinder, import the three-dimensional structure model of the ceramic core into the computer, and adjust the various printing parameters of the 3D printer. Then start printing, and the nozzle, powder supply cylinder, and working cylinder run according to the set program until the printing process is completed. Among them, the printing parameters of the 3D printing equipment are: printing layer height 0.15mm, binder is phenolic resin, and binder saturation 100%.
[0052] S3, after printing is completed, the printed core blank and the powder bed are placed in a drying oven and heated and cured at 200°C for 2h. After cooling, the core blank is taken out from the powder bed and the excess powder around it is cleaned. 15nm silica particles are added to the saturated solution of sodium sulfate and calcium chloride and dispersed evenly to obtain an infiltration solution, the mass ratio of sodium sulfate and calcium chloride is 9:1, and the amount of silica particles added is 5% of the total mass of the saturated solution of sodium sulfate and calcium chloride. Then the core blank is placed in the infiltration solution, taken out after infiltration for 4min at normal pressure, and then placed in a drying oven for drying.
[0053] S4, the infiltrated ceramic body is placed in a crucible and completely filled with spherical alumina particles, and then placed in a muffle furnace for high-temperature sintering. The sintering curve is sintered at 600°C for 2h, sintered at 35°C above the melting point of sodium chloride for 2.5h, and the heating rate is 4°C / min. Finally, the soluble core is obtained by cooling in the furnace.
[0054] Example 5
[0055] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core, which specifically includes the following steps:
[0056] S1, 75g of sodium chloride, 10g of sodium sulfate and 15g of calcium nitrate are mixed evenly, and then the salt is put into 600ml of stearic acid ethanol solution, the mass of stearic acid in the solution is 12g, stirred evenly and dried to obtain modified salt particles, and then the modified salt particles are crushed into 200 mesh, 500 mesh, 1000 mesh, 1500 mesh and 2000 mesh respectively to obtain modified salt powder.
[0057] S2, mix 200 mesh, 500 mesh, 1000 mesh, 1500 mesh, 2000 mesh silica and modified salt powder evenly as printing raw materials, wherein the modified salt powder is added in an amount of 90%, and the proportions of 200 mesh, 500 mesh, 1000 mesh, 1500 mesh and 2000 mesh powder are 20%, 20%, 20%, 20% and 20% respectively. Spread the mixed powder over the powder supply cylinder, import the three-dimensional structure model of the ceramic core into the computer, and adjust the various printing parameters of the 3D printer. Then start printing, and the nozzle, powder supply cylinder and working cylinder run according to the set program until the printing process is completed. Among them, the printing parameters of the 3D printing equipment are: printing layer height 0.25mm, binder is phenolic resin, and binder saturation 150%.
[0058] S3, after printing is completed, the printed core blank and the powder bed are placed in a drying oven and heated and cured at 220°C for 5 hours. After cooling, the core blank is taken out from the powder bed and the excess powder around it is cleaned. 100nm alumina particles are added to the supersaturated solution of sodium chloride and calcium chloride and dispersed evenly to obtain an infiltration solution, the mass ratio of sodium chloride to calcium chloride is 5.7:1, and the amount of alumina particles added is 20% of the total mass of sodium chloride and calcium chloride. Then the core blank is placed in the infiltration solution, taken out after infiltration under vacuum for 40s, wherein the vacuum degree is 40KPa, and then placed in a drying oven for drying.
[0059] S4, the infiltrated ceramic body is placed in a crucible and completely filled with spherical alumina particles, and then placed in a muffle furnace for high-temperature sintering. The sintering curve is sintered at 700°C for 3h, sintered at 50°C above the melting point of sodium chloride for 3h, and the heating rate is 6°C / min. Finally, the soluble core is obtained by cooling with the furnace.
[0060] Example 6
[0061] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core. The specific preparation method is the same as that of Example 3, except that in step S3, the soluble salt in the impregnation solution is only a saturated solution of sodium chloride.
[0062] Example 7
[0063] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core. The specific preparation method is the same as that of Example 3, except that in step S3, the amount of nano-ceramic particles added is 5% of the mass of the saturated solution of soluble salt.
[0064] Example 8
[0065] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core. The specific preparation method is the same as that of Example 3, except that in step S3, the amount of nano-ceramic particles added is 25% of the mass of the saturated solution of soluble salt.
[0066] Example 9
[0067] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core. The specific preparation method is the same as that of Example 3, except that the soluble salt solution in the impregnation liquid is an unsaturated solution.
[0068] Example 10
[0069] This embodiment provides a method for improving the performance and precision of a soluble core for droplet injection molding and a soluble core. The specific preparation method is the same as that of Example 3, except that the composition of the soluble salt includes: 30% calcium chloride and 70% sodium chloride, that is, 30g calcium chloride and 70g sodium chloride.
[0070] Comparative Example 1
[0071] This comparative example provides a soluble core and a preparation method thereof. The specific preparation method is the same as that of Example 3, except that: the soluble salt is not modified, that is, there is no step S1, and 80% sodium chloride and 20% calcium chloride are directly mixed and crushed to form soluble salt powders of 200 mesh, 500 mesh, and 1000 mesh.
[0072] Comparative Example 2
[0073] This comparative example provides a soluble ceramic core and a preparation method thereof, which specifically comprises the following steps:
[0074] S1. Mix 1000 mesh quartz and sodium chloride evenly, with the sodium chloride added in an amount of 15%. The mixed powder is dried at 80°C for 12 hours, and the powder is sieved after being taken out. Spread the sieved mixed powder all over the powder supply cylinder, import the three-dimensional structure model of the ceramic core into the computer, and adjust the various printing parameters of the 3D printer. Then start printing, and the nozzle, powder supply cylinder and working cylinder run according to the set program until the printing process is completed. Among them, the printing parameters of the 3D printing equipment are: printing layer height 0.05mm, binder saturation 80%.
[0075] S2. After printing, the printed ceramic core body and the powder bed are placed in a drying oven and heated and cured at 180°C for 3 hours. After cooling, the ceramic core body is taken out from the powder bed and the excess powder around it is cleaned. Subsequently, the ceramic core body is immersed in a 10% nano ZrO2 alcohol-based dispersion, impregnated for 3 minutes at normal pressure, and then taken out and placed in a drying oven at 70°C for 6 hours.
[0076] S3, put the impregnated ceramic body into a crucible, and fill it completely with spherical alumina particles, and then put it into a muffle furnace for high-temperature sintering. The sintering curve is sintered at 650℃ for 1h, 1100℃ for 1h, and the heating rate is 2℃ / min. Finally, the soluble ceramic core is obtained by cooling in the furnace.
[0077] Performance Testing
[0078] The bending strength of the soluble cores prepared in Examples 1-10 and Comparative Examples 1-2 was tested according to "HB5353.3-2004 Investment Casting Ceramic Core Performance Test Method Part 3", and the shrinkage of the soluble cores was tested according to "HB5353.2-2004 Investment Casting Ceramic Core Performance Test Method Part 2". See Table 1.
[0079] Table 1
[0080]
[0081] As can be seen from Table 1, compared with Example 3, Example 1 and 2, the flexural strength of Example 3 is better than that of Examples 1 and 2, and the sintering shrinkage is greater than that of Example 1, indicating that the composition of the impregnation solution and the multi-particle size gradation of the raw materials will affect the flexural strength of the soluble core, and the technical scheme described in this application can improve the flexural strength of the soluble core while ensuring a good sintering shrinkage. Compared with Example 3, Examples 4 and 5 show that the performance of the soluble core can be improved within the scope of the technical scheme defined in this application. Compared with Example 3, Example 6 shows that the flexural strength of Example 3 is better, indicating that the composition of the soluble salt in the impregnation solution will affect the performance of the soluble core. Compared with Example 3, Examples 7 and 8 show that the flexural strength and sintering shrinkage of Example 3 are higher than those of Examples 7 and 8, indicating that the amount of nano-ceramic particles added to the impregnation solution will also affect the performance of the soluble core. Comparing Example 9 with Example 3, it is shown that the saturation degree of the soluble salt solution in the impregnation solution can affect the performance of the soluble core, and when the soluble salt solution is a saturated solution or a supersaturated solution, the bending strength of the soluble core can be improved. Comparing Example 10 with Example 3, it is shown that the performance of the soluble core prepared under the soluble salt composition ratio specified in the present application is optimal. Comparative Example 1 is compared with Examples 3-5, which shows that modifying the soluble salt can improve the performance of the soluble core. Comparative Example 2 is compared with Examples 3-5, which shows that the present application can significantly improve the core performance compared to the prior art of simply combining ceramic powder and soluble salt to prepare a ceramic core.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the performance and precision of a soluble core in droplet injection molding, characterized in that: The following steps are involved: S1, mixing a soluble salt, a modifier and an organic solvent to obtain a modified salt powder, mixing ceramic powder and the modified salt powder to form a mixed powder, using a droplet injection molding process to prepare a core blank from the mixed powder, and heating and curing to obtain a core blank; S2, preparing a soluble salt solution, and adding nano-ceramic particles to the soluble salt solution, and mixing to obtain an impregnation solution; S3, placing the core blank into an impregnation liquid for impregnation treatment, drying and sintering at high temperature, and obtaining a soluble core after cooling in a furnace; The composition of the soluble salt includes, by mass percentage, 10%-20% of calcium salt and 80%-90% of other salts, the calcium salt includes calcium chloride and / or calcium nitrate, and the other salt includes one or a mixture of chlorides, sulfates, silicates, phosphates and metaphosphates; the modifier includes oleic acid and / or stearic acid; and the organic solvent is an alcohol solvent.
2. A method for improving the performance and precision of a soluble core in droplet injection molding as claimed in claim 1, characterized in that: The mass volume ratio of the soluble salt to the organic solvent is 1:3-6; the added amount of the modifier is 5%-15% of the mass of the soluble salt.
3. A method for improving the performance and precision of a soluble core in droplet injection molding as claimed in claim 1, characterized in that: The particle sizes of the ceramic powder and the modified salt powder are both 200 meshes-2000 meshes, and the mass percentage of the ceramic powder in the mixed powder is 10%-90%.
4. A method for improving the performance and precision of a soluble core in droplet injection molding as claimed in claim 3, characterized in that: The ceramic powder comprises a mixture of two or more particle sizes, and each particle size accounts for more than 15 wt.%.
5. A method for improving the performance and precision of a soluble core in droplet injection molding as claimed in claim 1, characterized in that: In step S3, the impregnation treatment time is 40 s to 4 min, the impregnation method is atmospheric pressure impregnation or vacuum impregnation, and the vacuum degree during vacuum impregnation is 0 to 40 KPa; the soluble salt solution is a saturated or supersaturated solution of soluble salt powder.
6. A method for improving the performance and precision of a soluble core in droplet injection molding as claimed in claim 5, characterized in that: The particle size of the nano-ceramic particles in step S2 is 15-100 nm, and the amount of the nano-ceramic particles added is 5%-20% of the mass of the soluble salt solution.
7. A method for improving the performance and precision of a soluble core in droplet injection molding as claimed in claim 1, characterized in that: In step S1, in the droplet jetting forming process, the binder is phenolic resin, the binder saturation is 90%-150%, the printing layer height is 0.07mm-0.25mm; the heating curing temperature is 190℃-220℃, and the heating curing time is 2h-5h.
8. A method for improving the performance and precision of a soluble core in droplet injection molding as claimed in claim 1, characterized in that: In step S3, the sintering is divided into two stages, namely, sintering at 550°C-700°C for 2 h-3 h, and then sintering within ±50°C of the melting point of the salt for 2 h-3 h, and the heating rate during the sintering process is 2-6°C / min.
9. A soluble core, characterized in that: The soluble core is prepared by a method for improving the performance and precision of a soluble core in droplet injection molding as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Aluminium oxide type depoling agent for directional solidification blade and depoling method
CN108889925A
Preparation method of water-soluble precision ceramic core for casting aluminum alloy
CN115477532A
Hot-press casting ceramic core and preparation method thereof
CN116924815A
Preparation method and removal method of silicon-based ceramic core
CN117602924A
Additive manufacturing method for ceramic core and shell integrated part
CN114180945A